Simultaneous Saccharification and Fermentation of Banana (Musa cuminata) Peel for Bioethanol Production - Tran, An T.T.; Nguyen, Quan D.; Le, Phung T.K. (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2015)
Banana (Musa acuminata) peel is discarded after the fruit processing process. Banana peel biomass can be used as raw material to produce bioethanol. In this research, banana peel was fermented by simultaneous saccharification and fermentation using Saccharomyces cerevisiae. Production of bioethanol was determined and the effects of various operation conditions which included different parameters in fermentation process: fermentation time, temperature, medium pH, concentration of yeast, enzyme loading, and shaking period. peel was cut, pretreated with H2SO4 2% and simultaneous hydrolyzed and fermented. Ethanol production was greatest (over 10,5%) when the initial pH of fermentation medium was adjusted to 4.5, 5% yeast supplement (8x107 cfu/ml), 7% cellulase (100 IU, v/v) loading, 24 hours and 37oC incubating,. The results illustrated that the simultaneous accharification and fermentation (SSF) of banana peel with S.cerevisiae has potential for industrial application.